Analyzed of Fixed Asset Management Based on Effectiveness and Efficiency at Office of Subdistrict Head Binjai - Catherine Evalina Tarigan; Junawan; Rahima Purba (Britain International for Academic Research (BIAR-Publisher), 2022)
This paper aims described analyzing the effectiveness and efficiency of fixed asset management at the Binjai District Office, Langkat Regency. This research is qualitative research with a descriptive approach. Data collection techniques in this study were the observation of the work of employees who handle fixed assets, interviews with employees who handle fixed assets, and documentation of documents related to fixed assets at the Binjai District Office of Langkat Regency. Based on the results of the research that has been carried out, it shows that: the results of the analysis of the effectiveness of fixed asset management at the Binjai District Office of Langkat Regency have not been effective as seen from the incompatibility of timeliness, the accuracy of cost calculations against applicable regulations.